Management of the preparation of student learning outcomes assessment instruments - Maula, Rohmatul; Ismiyati, Ismiyati; Ratnaningtyas, Dyah Ayu; Abdillah, Zuhdan Kamal (Research and Social Study Institute, 2023)
The purpose of this study is to examine more deeply the procedure for preparing student learning outcomes assessment instruments on archival management elements at SMK Negeri 9 Semarang in accordance with the mechanism for implementing the independent curriculum. The method used in this study is descriptive qualitative. Data analysis is carried out by collecting data, condensing data, presenting data, and drawing conclusions. The results showed that the preparation of assessment instruments had been carried out in terms of planning, organizing, actuating, and controlling. In planning, teachers develop learning tools and types of assessments to be used. On organizing, teachers make a cooperation, division of labor, and designing forms of assessment. In actuating, teachers do not compile assessment grids, but compile worksheets and assessment rubrics. In addition, the teacher only conducts qualitative analysis of question items. In controlling, teachers set criteria for achieving learning outcomes that refer to the criteria for achieving learning objectives. The conclusion of this study is that the preparation of learning outcome assessment instruments in terms of the planning, organizing, actuating, and controlling stages has been carried out in accordance with the mechanism for implementing the independent curriculum.